Imidazol-5-ones as a substrate for [1, 5]-hydride shift triggered cyclization. (21st January 2021) - Zaitseva, Elvira R.; Smirnov, Alexander Yu.; Myasnyanko, Ivan N.; Mineev, Konstantin S.; Sokolov, Anatolii I.; Volkhina, Tatyana N.; Mikhaylov, Andrey A.; Baleeva, Nadezhda S.; Baranov, Mikhail S.
Abstract : (2-Aminobenzylidene)-imidazolones were used as substrates for [1, 5]-hydride shift triggered cyclization under promotion by TiCl4 at room temperature. Abstract : 2-Dialkylamino-arylidene-imidazolones undergo intermolecular tandem [1, 5]-hydride shift and cyclization to form spirocyclic tetrahydroquinoline derivatives under TiCl4 promotion. Different substitutions on each of the aryl, amino and imidazole fragments are tolerated, which results in 20+ examples and 25–95% yields.